2016
DOI: 10.1136/jech-2016-207753
|View full text |Cite
|
Sign up to set email alerts
|

Testing the impact of local alcohol licencing policies on reported crime rates in England

Abstract: BackgroundExcessive alcohol use contributes to public nuisance, antisocial behaviour, and domestic, interpersonal and sexual violence. We test whether licencing policies aimed at restricting its spatial and/or temporal availability, including cumulative impact zones, are associated with reductions in alcohol-related crime.MethodsReported crimes at English lower tier local authority (LTLA) level were used to calculate the rates of reported crimes including alcohol-attributable rates of sexual offences and viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 25 publications
0
48
1
Order By: Relevance
“…However, the price of cigarettes has increased linearly over time, so its impact would have been removed by differencing the time–series (that is, using the difference between successive values of the outcome variables rather than the values themselves) 34. Several alcohol policies came into effect during the study period, including the removal of financial incentives aimed at encouraging general practitioners to screen their patients for heavy drinking, a ban on the sale of alcohol below the total cost of duty and value‐added tax (VAT) combined in May 2014, and strengthening of local alcohol licensing policies 55, 56, 57, 58. Tobacco policies include the Children and Families Act which, in 2015, made it an offence for an adult to buy tobacco for anyone aged under 18 years (including proxy purchasing) and the revised Tobacco Products Directive in 2016 which mandated the introduction of plain packaging, a ban on packs containing fewer than 20 cigarettes and stricter e‐cigarette regulation 59, 60.…”
Section: Discussionmentioning
confidence: 99%
“…However, the price of cigarettes has increased linearly over time, so its impact would have been removed by differencing the time–series (that is, using the difference between successive values of the outcome variables rather than the values themselves) 34. Several alcohol policies came into effect during the study period, including the removal of financial incentives aimed at encouraging general practitioners to screen their patients for heavy drinking, a ban on the sale of alcohol below the total cost of duty and value‐added tax (VAT) combined in May 2014, and strengthening of local alcohol licensing policies 55, 56, 57, 58. Tobacco policies include the Children and Families Act which, in 2015, made it an offence for an adult to buy tobacco for anyone aged under 18 years (including proxy purchasing) and the revised Tobacco Products Directive in 2016 which mandated the introduction of plain packaging, a ban on packs containing fewer than 20 cigarettes and stricter e‐cigarette regulation 59, 60.…”
Section: Discussionmentioning
confidence: 99%
“…This statutory requirement to assess overprovision is stronger than a non-statutory right to create 'cumulative impact zones' in England and Wales. A recent study of that provision found that the presence of effective cumulative impact zones was associated with a small (8 per 100,000 of the population) reduction in alcohol-related hospital admissions (20) and a reduction in alcohol-related crime (21).…”
Section: Introductionmentioning
confidence: 99%
“…Through alcohol licensing, local authorities (LAs) in England can shape alcohol environments in their local area. International evidence demonstrates that regulating the availability and accessibility of alcohol -for example through licensing -can reduce both alcohol consumption [1] and associated health and social harms [2][3][4][5][6]. The recognition in 2011 of a statutory licensing role for health authorities [7] and the 2013 reorganisation of public health into local government [8] in England, provided opportunities for public health to engage directly with the alcohol licensing process and potentially shape local alcohol environments [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are also opportunities for public health to engage with other LA stakeholders to shape local alcohol policy, such as a LA's Statement of Licensing Policy (SLP), or cumulative impact policies designed to restrict new licences or variations in areas of high outlet density [11][12][13][14][15]. Evidence indicates that restricting hours of sale, and policies to reduce the density of outlets are two key alcohol regulation levers at the local level, associated with reductions in alcohol-related hospitalisations [3,4], road traffic accidents and injury [2], violent and sexual crimes [3], and antisocial behaviour [1,2].…”
Section: Introductionmentioning
confidence: 99%